Legitimidade e representatividade em conselhos gestores : uma análise do Conselho Municipal de Cultura do Rio de Janeiro de 2007 a 2015 - Sessa, Tayane Reis Carvalho (2018)
The research aims to present and problematize the context of creation of the Municipal Council of Culture of Rio de Janeiro in 2009 based on the experiences of councilors and documentation published by the organization since then. It was intended to analyze its developments until the end of the term of office of the first representatives of civil society. The aim is to understand the reasons for the questioning of its legitimacy and representativeness and to suggest improvements, considering the experiences of the councilors, so that the organism can act effectively in the, controlling and monitoring of the cultural policies of the city of Rio de Janeiro.